Response of Mount Melimoyu glaciers, Chile, to dryer and warming climatic trends for Northern Patagonian region in last decades - Idalino, Filipe Daros; Rosa, Kátia Kellem da; Simões, Jefferson Cardia (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
In this paper were investigated area variations in glaciers on Mount Melimoyu (44ºS, 72ºW) in the period of 1970-2017, and possible relationships with the climate variability between 1950 and 2017. Optical data from Sentinel-2A, and elevation from Digital Elevation Model (DEM) ASTER-GDEM v.2 and area data from GLIMS inventory were used in GIS analyse. The temporal series of annual precipitation data by Explorador Climático - Chile, and temperature data of reanalysis from the University of Delaware were utilised for climate analysis. The glaciers area reduced from 80.97 km2 in 1970 to 52.14 km2 in 2017, equivalent to a 35.6% reduction in area, especially as for the glaciers located in the West, Southwest, North, and Northeast sectors, with losses between 65% and 44% of total area, and front-line elevation variations between 74 m and 570 m. The mean precipitation was 2539 mm in the period 1950‑2017 and is evidenced a tendency to decrease precipitation of approximately -18 mm per year. The temperature data show an annual average of 9.87°C and a continuous trend of increase in the region of 0.04°C between 1948 and 2017. The contrasts between glaciers in loss of area and variation of front line elevation are related to differences in area and geomorphometry of each glacier. These glaciers are similar in size, elevation and slope of the front sector, and the variations identified can be related to warm, and dryer trends for the region in the analysed period.